MANDIBULAR BONE QUALITY OF PANORAMIC RADIOGRAPHS IN HIV-INFECTED CHILDREN - Ria Noerianingsih Firman; Irna Sufiawati; Risti Saptarini Primarti; Aga Satria Nurrachman; Merry Annisa Damayanti (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: People living with HIV may have several pathologic conditions in its body and bone is one of the organs affected by HIV infection. HIV-infected patients have been associated frequently with osteoporosis and lower bone mineral density (BMD) which may lead to the increasing risk of bone fracture. This situation may become more complicated in children and young age as it will affect the long-term bone quality and development later in life until the peak BMD is reached. Objectives: The aim of this study was to measure the mandibular bone quality using the mandibular cortical index (MCI) and panoramic mandibular index (PMI) in panoramic radiographs of HIV-infected children. Method: This study used descriptive cross sectional research design which analyzed panoramic radiographs of HIV-infected children and measured its mandibular bone quality. Total 43 panoramic radiographs of HIV-infected children were observed and analyzed qualitatively using mandibular cortical index (MCI) and panoramic mandibular index (PMI) were used for the quantitave measurement, as it have been widely used for assesing mandibular bone quality in previous studies. Mandibular cortical index (MCI) has 3 categories of cortical bone quality: C1 (normal cortex), C2 (mildly to moderately eroded cortex), and C3 (severely eroded cortex), while the normal ratio of mental foramen-inferior border of mandible to mandibular cortical length in panoramic mandibuIar index is about 0.3. Result: Mandibular cortical index (MCI) of 43 HIV-infected children consist of 4 samples in C1, 38 in  C2, 1 in C3, while the panoramic mandibular index (PMI) of 43 HIV-infected children consist of 23 less than normal, 5 normal, 15 more than normal. Conclusions: The most number of mandibular cortical index (MCI) was C2 (mildly to moderately eroded cortex) and the most number of panoramic mandibular index (PMI) was less than normal of HIV-infected children.